If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3) + -4(3x + -1) + 6 + -1(5x + -2) + 3x = 0 Reorder the terms: 2(3 + x) + -4(3x + -1) + 6 + -1(5x + -2) + 3x = 0 (3 * 2 + x * 2) + -4(3x + -1) + 6 + -1(5x + -2) + 3x = 0 (6 + 2x) + -4(3x + -1) + 6 + -1(5x + -2) + 3x = 0 Reorder the terms: 6 + 2x + -4(-1 + 3x) + 6 + -1(5x + -2) + 3x = 0 6 + 2x + (-1 * -4 + 3x * -4) + 6 + -1(5x + -2) + 3x = 0 6 + 2x + (4 + -12x) + 6 + -1(5x + -2) + 3x = 0 Reorder the terms: 6 + 2x + 4 + -12x + 6 + -1(-2 + 5x) + 3x = 0 6 + 2x + 4 + -12x + 6 + (-2 * -1 + 5x * -1) + 3x = 0 6 + 2x + 4 + -12x + 6 + (2 + -5x) + 3x = 0 Reorder the terms: 6 + 4 + 6 + 2 + 2x + -12x + -5x + 3x = 0 Combine like terms: 6 + 4 = 10 10 + 6 + 2 + 2x + -12x + -5x + 3x = 0 Combine like terms: 10 + 6 = 16 16 + 2 + 2x + -12x + -5x + 3x = 0 Combine like terms: 16 + 2 = 18 18 + 2x + -12x + -5x + 3x = 0 Combine like terms: 2x + -12x = -10x 18 + -10x + -5x + 3x = 0 Combine like terms: -10x + -5x = -15x 18 + -15x + 3x = 0 Combine like terms: -15x + 3x = -12x 18 + -12x = 0 Solving 18 + -12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -12x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -12x = 0 + -18 -12x = 0 + -18 Combine like terms: 0 + -18 = -18 -12x = -18 Divide each side by '-12'. x = 1.5 Simplifying x = 1.5
| 15=3+-3n | | 106=-8k+6 | | 0.40x+0.27y= | | .8y-8=.4+16 | | 4(8m-7n)+6(3n-4m)= | | 16x-31=33 | | 6(2n-4)=-72 | | 38.6+y=54.3 | | 5(3+6x)=285 | | 0.1x-2=11 | | 0.35x+0.35y= | | 2(x+3)=2x+12-6 | | 3r^2-9r+6= | | 19+15j+1=-19+6(4j-19) | | -16h+-1=15 | | -30=5b | | 4a+16+9= | | -4(4p+2)=-72 | | 5x+5=12.5 | | .5x+7=3x-8 | | -2(p-9)=0 | | 5*x*5=125 | | 0.20y-0.20x= | | -80=4(-6n+4) | | 30-14*2+8= | | 8(-z-18)+8z=-4-14z | | 3x+5x+4+-4-x+7=88 | | 7(x+4)-(8x+3)=5(2x-1) | | 3z=96 | | 2(x+6)=3x-3 | | 17+3b=26 | | 20y+-16y-2=6 |